Contending materialist conceptions of the origin of the state: On the divide between Morgan and Engels - Matić Ivan (Srpska Politička Misao)
This paper will present a comparative analysis of two major materialist conceptions of the origin of the state, namely, those of Lewis Morgan and Friedrich Engels. The first part of the paper will offer a brief overview of the 17th century origins of this theory: the philosophical attempts to establish how the state came to be. Thereafter, we will look at how Morgan's innovative approach enabled tremendous progress on this issue, offering, if not the answer to the question of the state's origin, then at least the means of reaching it. The central part of the paper will present Engels' attempt to create a theory of his own, featuring aspects of both Marx's and Morgan's thought: in this regard, we will focus on the fundamental elements that are shared between Morgan's and Engels' theories. Finally, the subject of the last part of the paper will be the divergence between the two authors: here, we will examine the theoretical limitations of Engels' attempt to surpass Morgan's work and point to a number of errors that proceeded therefrom.